The private benefit of public funding: The FIFA World Cup, UEFA European Championship, and attendance at host country league soccer - Szymanski, S.; Drut, B. (Journal of Sports Economics, 2020)
This article examines attendance at league soccer matches before and after hosting an international soccer competition (the FIFA World Cup or the UEFA European Championships). We find significant increases in attendance at clubs that host games in these tournaments. We find smaller but often significant increases in attendance at other league clubs, suggesting that these events may drive fan interest. However, these results are patchy, and for some recent tournaments, they are negative. Our estimates of the private economic value of hosting, even in the most optimistic cases, are smaller than the cost of hosting as reported for recent tournaments.